"A More Thorough Resistance"? Coalition, Critique, and the Intersectional Promise of Queer Theory. (April 2020) - Gambino, Elena
Queer theorists have long staked their politics in an engagement with intersectionality. Yet intersectional scholars have been some of queer theory's most vocal critics, decrying its failure to adequately engage persistent inequalities. I approach this seeming paradox in three parts. First, I situate intersectionality within the field of critical theory, arguing that it shares critical theory's view of power. Both traditions, I argue, understand power to generate the very marginalized figures that it subordinates. Second, while intersectional and queer theories share this critical insight, the two frameworks offer fundamentally different understandings of what constitutes a democratic politics of redress. Where intersectional theorists promote coalition-building between differently marginalized subjects, queer theorists tend to figure sexually marginalized subjects as exemplary democratic agents. Finally, I argue that this slippage in conceptions of democracy has had negative consequences for critical theory and highlights the difficult but essential role of coalition as a political resource.